2018
DOI: 10.1002/sia.6484
|View full text |Cite
|
Sign up to set email alerts
|

Study on surface structure of plasma‐treated polydimethylsiloxane (PDMS) elastomer by slow positron beam

Abstract: In this paper, the variations in surface structure of polydimethylsiloxane elastomers before and after argon plasma treatments have been investigated by X‐ray photoelectron spectroscopy, slow positron beam, and scanning electron microscope. An inorganic silica‐like layer was probed by X‐ray photoelectron spectroscopy after 3 minutes or longer time of treatments, and the sample surface turned into totally hydrophilic. Short time (1 and 2 min) plasma exposure mainly removed preexisting low molecular weighted (LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…We deduced that the cracks originate from the rupture of the silica‐like layer. Because this inorganic layer is brittle, it finally fractures after long‐term corona or plasma exposure . When the treatment time is longer (84 or 135 hr), pores cannot be found due to the massive generation of particle‐like species, as shown in Figure e–f.…”
Section: Resultsmentioning
confidence: 99%
“…We deduced that the cracks originate from the rupture of the silica‐like layer. Because this inorganic layer is brittle, it finally fractures after long‐term corona or plasma exposure . When the treatment time is longer (84 or 135 hr), pores cannot be found due to the massive generation of particle‐like species, as shown in Figure e–f.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the polymer surface would be hydrophilic state immediately after plasma modification, but the surface would return to hydrophobic state after a few hours or days, which is called hydrophobic recovery . The hydrophobic recovery could be attributed to the diffusion of hydrophobic low molecular weight molecules or the relaxation of hydrophobic chain segments ,. In our previous study, it was found that the rheological property of EVA during the melt extrusion process is influenced by the vinyl acetate (VA) contents .…”
Section: Figurementioning
confidence: 99%
“…Due to its properties, PDMS is a polymer material used in many applications, ranging from biomedicine to power engineering [ 1 , 2 , 3 , 4 , 5 ]. In addition, the properties of its surface can be changed via plasma modification, including corona plasma, DBD, and RF PACVD [ 1 , 4 ]. Laser treatment and UV radiation are also used for this purpose [ 1 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%